UJI EFEKTIVITAS Trichoderma harzianum DAN PEMBERIAN ARANG BATOK KELAPA SEBAGAI PENGENDALIAN HAYATI PENYAKIT LANAS (Phytophtora nicotianae de Hann ) PADA TANAMAN TEMBAKAU DELI - Indra Hardian Matondang; Lahmuddin Lubis; Mukhtar Iskandar (Jurnal Agroekoteknologi, 2014)
Test Effectiveness of Trichoderma harzianum and Coconut Shell Charcoal Granting of controlBiological Disease As Lanas (Phytophtora nicotianae de Hann) In Tobacco Plants Deli. The studyaims to determine the concentration of T. harzianum and charcoal administration is most effectivein controlling diseases in plants Tobacco P.nicotianae Deli. The experiment was conducted at theExperimental Farm Deli Sampali Tobacco Research Institute, Medan. This research used arandomized block design factorial with two factors and three replications. The first factor T.harzianum (T) consists of (T0) without treatment, (T1) T.harzianum that in cultures on corn mediawith a dose of 10 g / plant, (T2) T.harzianum that in cultures on corn media with a dose of 15 g /plant, (T3) T.harzianum that in cultures on corn media with a dose of 20 g / plant and the secondfactor consists of charcoal administration (A0) without treatment, (A1) coconut charcoal with adose of 20 g / plant. The results showed the highest percentage of attacks are on treatment T0A0amounting 99.71% and the lowest percentage of attacks are on treatment T3A1 (T.harzianum that incorn cultured on medium with a dose of 20 g / plant and coconut shell charcoal with a dose of 20 g /plant ) by 0.71%. The highest number of leaves found in treatment T3 (T.harzianum that in cultureson corn media with a dose of 20 g / plant strands at 11.67 and the lowest at treatment T0 (control) of7.17strands.Keywords: T.harzianum, coconut Shell charcoal, P.nicotianae, TobaccoDeli